The effect of using some teaching methods in learning the skill of basketball scoring - Shaima Jasim Mohamed (College of Physical Education and Sport Sciences, 2011)
The aim of the research is to identify the effect of using the methods (the traditional method, the cooperative method, the reciprocal method) in learning the skill of peaceful scoring in basketball for second-stage students in the Department of Physical Education / Al-Mustansiriya University. And to identify the differences in the post tests of the skill of peaceful scoring in basketball for students of the second stage in the Department of Physical Education / Al-Mustansiriya University using the methods (the traditional method, the cooperative method, the reciprocal method) knowing the best methods in learning the skill in question. The researcher hypothesized: There are statistically significant differences between the tribal tests and the post tests of the skill of peaceful scoring in basketball using the methods (the traditional method, the cooperative method, the reciprocal method). And there were statistically significant differences between the post tests of the skill of peaceful scoring in basketball using the methods (the traditional method, the cooperative method, the reciprocal method). The theoretical framework included addressing the teaching methods and the basic features of the group of teaching methods, as well as the cooperative method, the reciprocal method, the skill of peaceful scoring, and similar studies that dealt with these two methods. As for the research procedures, the experimental method was used to suit the nature of the problem, and the research sample was chosen from the original research community, represented by its second-stage request in the Department of Physical Education in the College of Basic Education. Group using the collaborative method. And the second experimental group: This group was taught using the reciprocal method. And the third control group: where this group was taught the adopted method, that is, the traditional method. The peaceful basketball scoring test was used. The researcher concluded: that the educational curriculum prepared according to the methods used in the research has a positive and effective effect in teaching some types of basketball scoring. The experimental group outperformed the control group in the skill performance of some types of basketball scoring.